Mapeamento da população em situação de rua na cidade do Rio de Janeiro: uma proposta metodológica - João Grand Junior; João Gabriel Gomes Gonzaga; Thácio Henrique’s Almeida (Confins)
The topic of the homeless population is characterized as a central debate for public administration in contemporary metropolises. The Covid-19 pandemic has exacerbated the picture of social vulnerabilities in the world, especially in peripheral and semi-peripheral countries. In this context, the issue of the homeless population becomes even more complex and challenging for cities as it is observed, on the one hand, the rising precarization of living standards, and on the other, the diminishing capacity of authorities to implement effective and timely interventions. In the city of Rio de Janeiro, the public health emergency of Covid-19 has intensified the situation of the economic crisis, which was already affecting the city following the Olympics, and has further contributed to an increase of the homeless population across the city. With the aim of improving the production of reliable data and more precise diagnostics in order to inform the implementation of more assertive public policies, The Municipal Secretary of Social Assistance and Human Rights and the Pereira Passos institute, have joined forces to carry out a wide-reaching study: A Census on the Homeless Population.This article outlines a new methodology which was used to develop the scripts for the census. Using a participatory mapping approach, we aim to present a dynamic and systematic picture of the spatiotemporal situation of homelessness in the city of Rio de Janeiro, highlighting the strategies and instruments developed.